A Three-dimensional Numerical Study Using (FLAC3D) of Tensile Load Capacity of Piles - رامي العبدة; رشا أحمد (Latakia University Journal -Engineering Sciences Series, 2022)
Pile foundation are used when the bearing capacity of the soil is insufficient in the presence of the shallow foundations. Practically, the piles that exposed to compressive stresses are more common and frequently used but also the piles that exposed to tensile stresses are used in many cases and have a great importance. the resistance of the piles to the tensile stresses directly affects the stability of facilities whether in retaining walls or in installations exposed to horizontal forces and upheaval moment because of the wind, the waves [11], also the study of this case for piles allows us to estimate the force required to be applied to the pile to remove it from the soil after finishing the use of piles in the temporary support. There are several methods for determining the tensile resistance of piles such as experimental methods (laboratory or field ), analytical methods, and numerical methods. The experimental methods (especially the field methods) are the closest to reality but they are so expensive and need high accuracy in implementation, as for the analytical methods depend on hypotheses or approximate relationships so they may not give accurate results of reality when generalized. The numerical methods provide high accuracy and simulate reality, saving time and effort, therefore, in this paper, we will work on creating and developing a 3D model which will be used to determine the tensile strength of the piles. For modeling, the program was used (FLAC(3D) v3.261), which depends on the finite difference method. We established a numerical analysis for a concrete pile in a homogeneous soil and exposed to a tension force and we figured the tensile strength of the pile. The model was achieved in this research has been validated by the results of the field study [11] and laboratory study [13]. Then a parametric study was conducted to verity the effect of some parameters that may affect the tensile strength of the pile.